Evaluasi Program Baca Tulis dan Hafalan Qur’an (BTHQ) di MI Ummu Kaltsum Menggunakan Model CIPP (Context, Input, Process and Product) - Fitri, Ummu Nurul; S, Syamsudduha (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article aims to evaluate the implementation of the Read Write and Memorize Qur'an Program (BTHQ) at MI Ummu Kaltsum, Biringkanaya District, Makassar City using the CIPP (Context, Input, Process, Product) evaluation model. The method used is a qualitative approach with an evaluative descriptive design. Data collection was conducted through interviews and observations with the principal, program coaches, and parents/guardians of students. The evaluation results show that the BTHQ program has been running in accordance with the background and needs of religious education, although there are some obstacles, such as limited time and facilities. The input evaluation identified that the program coaches have adequate competence, but the limited number of coaches and facilities are a challenge in achieving the program objectives optimally. The program implementation process runs by using the Iqra' method, although there are obstacles such as damage to facilities and limited time. Product evaluation shows that the achievement of program objectives has not been maximized, with some students not yet fluent in reading the Qur'an. The implication of the results of this study is the need for improvement in terms of time allocation, additional coaches, and improved infrastructure to increase the effectiveness of the BTHQ program in the future.